Taste in Motion: The Effect of Projection Mapping of a Boiling Effect on Food Expectation, Food Perception, and Purchasing Behavior - Suzuki, Yuji; Narumi, Takuji; Tanikawa, Tomohiro; Hirose, Michitaka (Frontiers in Computer Science, 2021)
The appearance of food affects its taste. Many studies have examined how to improve the taste of foods by manipulating their appearance. Most of those studies have focused on static appearances, such as color and texture; however, the impact of the dynamic appearance has not been explored. In this study, the perceptions (sweetness, sourness, saltiness, spiciness, temperature, deliciousness) and value judgments (the price of food, appetite) perceived from food before and after tasting with a projection-based dynamic boiling texture were investigated. The results revealed that the dynamic texture influences expectations for saltiness, spiciness, temperature, deliciousness, price, and appetite before eating the meal and perceived saltiness, spiciness, and appetite when eating. In addition, its influence on the consumers' behavior was also investigated through an empirical user study in a restaurant. The results indicated that the consumers had a greater tendency to order the meal when they saw it with the projection-based boiling effect. From these, this study demonstrates the effect of projection mapping of a boiling effect on food expectation, perception and consumer behavior.